Increasing the Village Apparatus's Capacity for Administrative Services in Tanjung Solok Village - Tawakkal, M. Iqbal; Abidin, Zaenal; Wandi, Wandi; Wargo, Wargo (CV. Zabags Qu Publish, 2024)
This study aims to analyze the capacity of Tanjung Solok village officials in providing administrative services and identify solutions to improve their performance. The method used is a descriptive qualitative approach, with data collection through in-depth interviews, field observations, and documentation studies. The findings show that village officials experience obstacles in administrative skills, lack of understanding of technology, and lack of infrastructure support, which has an impact on the quality of public services. The recommendations of this study include the implementation of periodic training programs for skill development, improvement of technological infrastructure, and strengthening the leadership of village heads through a participatory approach. In addition, it is recommended to build a monitoring system that involves the community as feedback to ensure that services remain in accordance with community expectations. With these steps, it is hoped that the capacity of village apparatus can increase, so that administrative services become more efficient and effective